Current – voltage measurements of Al/a-Se/Au Schottky diode solar cells: DOI: 10.48129/kjs.12729 - Fdhala, Mayyada; Hemed, Ayser; Al-Ansari, Ramiz; Al-Haddad, Raad; Abbas, Rasha (Kuwait Journal of Science, 2022)
Schottky diode Al/a-Se/Au as solar cells (SC) were made up by thermal evaporation technique (TET) on glass thin slide at a substrate under vacuum (vacuum value equal to mbar). The Schottky barriers have been prepared with different thicknesses (300,500 and 700) nm in room temperature and (343) K annealing temperature. The current-voltage (I-V) physical properties of the Schottky barrier have got that the rectification properties and approved as solar cell which have been develop with the increasing (annealing temperatures and thickness of layers of Schottky diode). Experience under lighting shows good efficiency (η), which increased linearly with both thickness and annealing temperatures from (0.0318% to 4.064%) and from (0.0318% to 0.4778%). This is for three values of lighting power density (160, 230, 400) in which the behave is similarly. The best efficiency obtained in this work was (12.407)% at a power density of 230 , with thickness 500nm and 343K annealing temperature. Also (15.286)% at 400 , with thickness700nm and 343K annealing temperature.